Coexistence of superficial carcinogenesis of resident epithelium besides neuroendocrine neoplasm of the digestive tract. (20th January 2022) - Kuwano, Hiroyuki; Yokobori, Takehiko; Ide, Munenori; Saeki, Hiroshi; Sohda, Makoto; Sakai, Makoto; Yoshida, Tomonori; Kuriyama, Kengo; Ogata, Kyoichi; Ogawa, Hiroomi; Okada, Takuhisa; Miyazaki, Tatsuya; et al.
Abstract: Background & Aims: Mixed neuroendocrine–non‐neuroendocrine neoplasm (MiNEN) is a rare neuroendocrine neoplasm (NEN) comprising dual neuroendocrine and non‐neuroendocrine components. Although the coexistence pattern of neuroendocrine and non‐neuroendocrine components in definitive MiNEN is thought to overlap, there may be a coexistent pattern of both components, such as superficial carcinoma adjacent to NEN. The present study evaluated the histopathological findings of the coexistence pattern of superficial carcinomas adjacent to NENs in the esophagogastrointestinal tract. Methods: From 2000 to 2019, 35 serial NEN resections of the esophagus ( n  = 9), stomach ( n  = 3), and large intestine ( n  = 23), respectively, were performed at Gunma University Hospital. Borderline areas between NEN and resident superficial epithelium were observed in the 35 serial NEN cases as well as two additional cases from affiliated hospitals. Results: Among the 35 serial NEN samples, squamous cell carcinomatous/dysplastic components were identified 77.8% (7/9 cases) of esophageal NENs, and adenocarcinomatous areas were seen in 66.7% (2/3 cases) of gastric NENs and 26% (6/23 cases) of colorectal NENs. Thus, all superficial carcinomatous components adjacent to NENs were observed as squamous cell carcinoma/dysplasia in esophagus and adenocarcinoma in stomach and large intestine, which showed histological characteristics as the resident epithelial pattern in each organ. Conclusions: These findings suggested a potential "paratransformation" or "bystander effect" in resident epithelium by NENs. Thus, "bystander carcinogenesis" could be a pathogenic mechanism of resident epithelium transformation adjacent to NENs in the esophagogastrointestinal tract. Abstract : All superficial carcinomatous components adjacent to neuroendocrine neoplasms were observed as squamous cell carcinoma/dysplasia in esophagus and adenocarcinoma in stomach and large intestine, which showed histological characteristics as the resident epithelial pattern in each organ. Therefore, bystander carcinogenesis could be a pathogenic mechanism of resident epithelium transformation adjacent to neuroendocrine neoplasms in the esophagogastrointestinal tract.